Relative age effects in elite Brazilian track and field athletes are modulated by sex, age category, and event type - Lucas Savassi Figueiredo; Drumond Gilo da Silva; Bruno Henrique Góes Oliveira; Arthur Gomes Ferreira; Petrus Gantois; Fabiano de Souza Fonseca (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study investigated the Relative Age Effect (RAE) in Brazilian track and field athletes based on sex, age category (U-16, U-18, U-20, U-23 and senior), and event type (sprints/hurdles, middle distance, long-distance, jumps, throws). Methods: Data from 2.259 male and 1.776 female elite track and field athletes, ranked top-50 in events held by the Brazilian Track and Field Confederation in 2019 were analyzed. To determine RAE athletes were divided into four quarters based on their months of birth, considering January 1st the cut-off date. The influence of sex, age category, and event types in the pervasion of RAE in Brazilian track and field athletes was assessed through Chi-squared tests. Results: Athletes born closer to the cut-off date were more frequent than athletes born further from this date were in male youth categories. This effect reduced as categories increased, even reversing in the senior category. Finally, RAE was more frequent in events in which athletic performance relies more on strength, speed, and power, which is the case of sprints/hurdles, jumps, and throws. Conclusion: RAE is particularly prevalent in young male Brazilian track and field athletes, which indicates that many potentially talented athletes are overlooked in youth tryouts because they were born months away from the cut-off date. Policies that reduce the disadvantages faced by relatively younger athletes are warranted in order to avoid the loss of potential sports talents.